Effects of Perception and Attitude of Entrepreneurs to Green Tourism: Ban Prasat Homestay - วิวัฒน์เจริญ วิมล (Ratchaphruek Journal, 2019)
The research was aimed to study perception and attitude of accommodation entrepreneurs towards green tourism: Ban Prasart Homestay. Green tourism under 7 greens concept. The sample used in the study included homestay entrepreneurs. The tools of data collection were a questionnaire and an interview. The structured questionnaire that had passed the test of validity and reliability quality confirmed by Cronbach’ alpha values of above 0.802. The structured questionnaire that had passed the test of understanding by KR20 values 0.62. The statistics used for analyzing data included descriptive statistics and chi-square test. It was found that the most of homestay entrepreneurs have perception about green tourism in the medium level. The samples have positive attitude of homestay entrepreneurs toward green tourism with = 4.16. There was no statically significant relationship between sex, age, education, marital status, income, and time of operation and attitude of homestay entrepreneurs toward green tourism. The strengths of homestay entrepreneurs were green tourism policy, cultural resources, traditions, the way of life of community, the role of community’s leaders, participation of people in community, Homestay Standard Thailand, awards from abroad and Ban Prasart Green Tourism Activity. The weaknesses were English communication, Public Relations. The opportunities were the policy of The National Tourism Policy Committee and the trend of Green tourism. The threats were the decreasing of homestay entrepreneur’s numbers, the increasing of new homestay’s numbers by OTOP Nawatwithi Project, the insufficiency of budget for public utility development and low season period. Keywords : Perception, Attitude, Entrepreneur, Green Tourism